A Fundamental Understanding of Catechol and Water Adsorption on a Hydrophilic Silica Surface: Exploring the Underwater Adhesion Mechanism of Mussels on an Atomic Scale - Mian, Shabeer Ahmad; Yang, Li-Ming; Saha, Leton Chandra; Ahmed, E.; Ajmal, Muhammad; Ganz, Eric (AMER CHEMICAL SOC, 2014)
Mussels have a remarkable ability to bond to solid surfaces under water. From a microscopic perspective, the first step of this process is the adsorption of dopa molecules to the solid surface. In fact, it is the catechol part of the dopa molecule that is interacting with the surface. These molecules are able to make reversible bonds to a wide range of materials, even underwater. Previous experimental and theoretical efforts have produced only a limited understanding of the mechanism and quantitative details of the competitive adsorption of catechol and water on hydrophilic silica surfaces. In this work, we uncover the nature of this competitive absorption by atomic scale modeling of water and catechol adsorbed at the geminal (001) silica surface using density functional theory calculations. We find that catechol molecules displace preadsorbed water molecules and bond directly on the silica surface. Using molecular dynamics simulations, we observe this process in detail. We also calculate the interaction force as a function of distance, and observe a maximum of 0.5 nN of attraction. The catechol has a binding energy of 23 kcal/mol onto the silica surface with adsorbed water molecules.
Keywords: DENSITY-FUNCTIONAL THEORY; MARINE MUSSEL; CROSS-LINKING; PROTEIN; DOPA; MODEL; ELEMENTS